Using information problem-solving activities to teach: an exploratory study designed to improve teacher competencies related to internet use in the classroom. Issue 2 (15th March 2021) - Hinostroza, J. Enrique; Ibieta, Andrea; Labbé, Christian
ABSTRACT: Studies show that students and teachers frequently use the internet for learning and teaching, but that both lack the skills necessary to utilise it effectively. The authors designed an intervention to develop teachers' information search skills and improve the information problem-solving using the internet (IPS-I) tasks that they implement with their students. Twenty-one Grade 7 teachers participated in a blended learning workshop and implemented IPS-I activities in their courses using a specially designed internet search engine. The results show that teachers improved certain search strategies and the IPS-I tasks that they implemented by conceiving of the internet as a tool for learning. They incorporated objectives associated with the development of students' higher order skills, included question development steps in the tasks, and monitored students' search activities and products. The authors highlight the aspects of the internet search software that contributed to these changes and opportunities for teacher training programmes.